Resurrecting deadly carrots: towards a revision of Thapsia (Apiaceae) based on phylogenetic analysis of nrITS sequences and chemical profiles. (13th March 2014) - Weitzel, Corinna; Rønsted, Nina; Spalik, Krysztof; Simonsen, Henrik Toft
<x xml:space="preserve">Abstract</x> Thapsia is a small genus of herbaceous perennials in Apiaceae. Thapsia occurs around the Mediterranean, extending from the Atlantic coasts of Portugal and Morocco to Crete and other Greek Islands. Thapsia is commonly known as deadly carrot because of its poisonous effects. The resin from Thapsia spp. has been used in traditional medicine and included in European pharmacopoeias, and several species contain biologically important sesquiterpene lactones, such as thapsigargin. Accordingly, Thapsia has for decades been subject to chemical investigations searching for new specialized metabolites with potential as drug leads. However, no generally accepted taxonomic concept of > 40 species and synonyms exists. To address the phylogenetics and circumscription of Thapsia, we present the first molecular phylogenetic hypothesis of Thapsia based on sequences of the nuclear ribosomal internal transcribed spacer (nrITS) region from 50 accessions of Thapsia and representatives of all currently recognized genera in subtribe Daucinae. Phylogenetic analysis using maximum parsimony and Bayesian inference resulted in a well‐resolved topology with strong support for inclusion of all the species studied here from Ammodaucus, Distichoselinum, Elaeoselinum, Guillonea and Margotia in Thapsia, in correspondence with previous phylogenetic studies of Apiaceae. Elaeoselinum is not monophyletic. Clades in Thapsia correlate well with previous observations of groupings based on the occurrence of biologically important sesquiterpene lactones, such as thapsigargin and thapsane and derivatives thereof. The result of the phylogenetic analysis necessitates nomenclatural adjustments. Thus, we propose a broader generic concept for Thapsia. Here T. asclepium, T. gummifera and T. tenuifolia are reinstated, new name combinations are made for T. leucotricha, T. scabra and T. thapsioides, and one new species, T. smittii, is established from T. maxima type II. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 174, 620–636.